EFEKTIFITAS PENERAPAN LEARNING TO WORK PROFESIONALISME DAI WAHDAH ISLAMIYAH DI MAKASSAR - Hamiruddin; Bin Bahe, Muhammad Amir; AB, Syamsuddin (Jurnal Dakwah Tabligh, 2023)
The effectiveness of learning to work professionalism of preachers among Wahdah Islamiyah provides an overview of what Wahdah Islamiyah preachers do, both to know and. The type of research is qualitative with the method used being descriptive qualitative with a phenomenological approach. Primary data sources by conducting direct interviews with preachers, managers of preacher training, and lajnah preachers who are responsible for controlling the activities and existence of Wahdah Islamiyah preachers in the regions. The results of this study indicate that: Learning to work is an effective activity to increase the professionalism of preachers at Wahdah Islamiyah if the preachers are active in carrying out da’wah activities in the regions. Then there is control from the heads of the regions or regions where the preacher preaches, besides that there is also control from the center. From the results of this study, it can be concluded that the learning-to-work process carried out by alumni of the Wahdah Islamiyah preaching training can improve their professionalism.